The Motivations of Using Facebook by Old People and their Achieved Need - حسين أحمد عبد الستار (ALBAHITH ALALAMI, 2017)
This research deals with the motives of the use of Facebook by elderly people and the achieved needs, which leads the researcher to ask an important question: why an old persons use Facebook and are the achieved needs through which they got? The research aims to find out the habits and patterns of using Facebook by old men and stands on the main motives of the elderly in their use of Facebook. It also identifies the most prominent needs that have been made for the elderly as a result of their use of Facebook. The research is a descriptive one in which the researcher uses survey method to achieve the desired goals. The researcher has chosen a group of old men from Diyala province. The total sample number is about 120 people to clear their views through the questionnaire. The researcher has selected those who are using Facebook and their age is 60 years and above. They can read and write and having a scientific certification. The researcher has reached to the following results: 1 - The respondents confirm that the main motive of their use of Facebook is linked to the aim of knowing current events, and then comes the goal of communicating and following-up news of friends and relatives. • Respondents agreed that the most prominent achieved needs by the use of Facebook are: it makes them familiar with what is going on in the world around them and it helps them to create a communicative atmosphere with their friends and relatives.